2019
DOI: 10.1186/s13018-019-1427-z
|View full text |Cite
|
Sign up to set email alerts
|

Gamma 3 U-Blade lag screws in patients with trochanteric femur fractures: are rotation control lag screws better than others?

Abstract: BackgroundIntramedullary hip nails may be classified as blades or screws depending on the type of lag screw used. Recently, a combination of lag screw types with a U-clip insertion has also been used. The purpose of this study was to evaluate the clinical and radiological outcomes of these new screw types.MethodsA total of 185 patients with trochanteric femoral fractures (age ≥ 65 years) who underwent surgery with intramedullary nails were selected. Surgeries with InterTrochanteric/SubTrochanteric (ITST), Prox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(45 citation statements)
references
References 20 publications
1
42
0
2
Order By: Relevance
“…However, Massoud 3) have suggested that an anti-rotational screw should be added to control rotational instability after surgery because the lag screw has potential to rotate the rotationally unstable femoral head during its insertion. Authors of recent reports included in this study argue that the antirotational effect of implant should be taken into account when selecting an implant for the fixation of these rotationally unstable fractures [14][15][16][17][18][19] .…”
Section: Ota/ao: A1mentioning
confidence: 99%
See 4 more Smart Citations
“…However, Massoud 3) have suggested that an anti-rotational screw should be added to control rotational instability after surgery because the lag screw has potential to rotate the rotationally unstable femoral head during its insertion. Authors of recent reports included in this study argue that the antirotational effect of implant should be taken into account when selecting an implant for the fixation of these rotationally unstable fractures [14][15][16][17][18][19] .…”
Section: Ota/ao: A1mentioning
confidence: 99%
“…Proximal fragment included part of the lesser trochanter (black arrow). (B B) Schematic figure depicting the radiograph in the study of Yoo et al 19) . The lesser trochanter fragment is displaced (black arrow).…”
Section: Ota/ao: A1mentioning
confidence: 99%
See 3 more Smart Citations